Pendekatan Holistik Pengembangan SDM dan Kepuasan Kerja Dosen Universitas La Tansa Mashiro - Puri Rohmatulloh (E-Journal Studia Manajemen, 2026)
This study examines the relationship between CPD, training quality, self-efficacy, leadership support, and tridharma workload with lecturer job satisfaction (N = 85) using correlation analysis, linear regression, and mediation–moderation testing. The results indicate significant positive associations between training quality (β_std ≈ 0.26, p < 0.001) and self-efficacy (β_std ≈ 0.26, p < 0.001) with job satisfaction; CPD and leadership support showed smaller positive effects, while tridharma workload was negatively correlated (β ≈ –0.06, p < 0.001) and moderated the effectiveness of CPD. These findings support the role of resources within the Job Demands–Resources framework; however, causal interpretations are limited by the cross-sectional design. To strengthen inferential validity, it is recommended to: (1) report standardized effect sizes and 95% confidence intervals, test regression assumptions, and assess VIF; (2) apply bootstrap or SEM for mediation testing; (3) center variables before interaction analysis; and (4) employ qualitative triangulation or longitudinal designs to enhance generalizability and policy relevance